Strategi Komunikasi GoFood Bertahan Saat Pandemi COVID-19: Analisis Difusi Inovasi GoFood Indonesia - Nadila Zahara Faradysa (JURNAL LENSA MUTIARA KOMUNIKASI, 2022)
The pandemic caused by the coronavirus (COVID-19) caused difficulties experienced by various sectors of life. Indonesian government has taken a policy to limit the movement of people to suppress the spread of COVID-19, which has an impact on limiting daily activities. GoFood as a pioneer of online food delivery (OFD) services seeks to overcome the crisis of public trusts in the application of health protocols when using these services. The purpose of this study is to find out how GoFood's communication strategy can survive in the midst of a pandemic through innovation. This research uses a qualitative approach with descriptive case study research methods. The results showed that the communication strategy used was the J3K campaign. GoFood has also created innovations that support the campaign by creating Self Register feature for merchant partners applicants without meeting face-to-face, Hygiene Sticker feature for merchant partners who apply health protocol standards, ‘Posko Aman’ service for driver partners, Contactless Delivery feature, GoFood Pickup feature, and Ready to Cook feature. GoFood also utilise of its communication channels to spread messages that are consistent and correlated with each other. To improve service, the researcher suggests GoFood to make innovations that can monitor and evaluate the discipline of merchant partners in implementing health protocols.